2019
DOI: 10.1371/journal.pone.0210280
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of Lyme disease and the cost-effectiveness of Lyme disease interventions: A scoping review

Abstract: IntroductionWhile Lyme disease (LD) is mostly treatable, misdiagnosed or untreated LD can result in debilitating sequelae and excessive healthcare usage. The objective of this review was to characterize the body of literature on the economic burden of Lyme disease (LD) and the cost-effectiveness of LD interventions, such as antibiotic treatment and vaccination.MethodsWe followed Joanna Briggs Institute scoping review methodologies. We systematically searched terms related to LD, economic evaluations, costs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 40 publications
1
58
0
Order By: Relevance
“…Lyme borreliosis, a tick-borne multisystemic illness caused by the spirochete Borrelia burgdorferi sensu lato, has grown into a major public health problem [1][2][3][4][5]. The frontline treatment for Lyme disease is the administration of antibiotics [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Lyme borreliosis, a tick-borne multisystemic illness caused by the spirochete Borrelia burgdorferi sensu lato, has grown into a major public health problem [1][2][3][4][5]. The frontline treatment for Lyme disease is the administration of antibiotics [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Using the cost-per-ED visit estimate from that study, the Wisconsin ED visits would have cost $2.9 million, compared to our $3.1 million estimate (2018 dollars). Recent studies quantified the national burden of Lyme disease at $786 million to $1.3 billion annually (Adrion et al, 2015;Mac et al, 2019); our estimate for Michigan ($8.0 million) reflects the burden of a single, low-incidence state. For allergenic oak pollen, our estimate of ED costs in North Carolina ($0.6 million) is consistent with a comparable national estimate ($12.2 million in 2018 dollars; Anenberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Public health burdens due to Lyme disease are not unique to the USA. A recent comprehensive review found Lyme disease-associated expenditures of tens of millions of euros in several European countries [10]. The combined public health impact of all tick-borne diseases remains mostly unquantified.…”
Section: Introductionmentioning
confidence: 99%